2021
DOI: 10.3390/electronics10151834
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Machine Learning Techniques in IoT-Based Architecture for the Monitoring and Prediction of COVID-19

Abstract: From the end of 2019, the world has been facing the threat of COVID-19. It is predicted that, before herd immunity is achieved globally via vaccination, people around the world will have to tackle the COVID-19 pandemic using precautionary steps. This paper suggests a COVID-19 identification and control system that operates in real-time. The proposed system utilizes the Internet of Things (IoT) platform to capture users’ time-sensitive symptom information to detect potential cases of coronaviruses early on, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The performance of the models is measured using root-mean-square error (RMSE) and R (correlation coefficient). The hybrid model of PNN and RBFNN performed better than all [ 50 ]. The authors have suggested the IoT-based identification and control system in real time.…”
Section: Related Workmentioning
confidence: 99%
“…The performance of the models is measured using root-mean-square error (RMSE) and R (correlation coefficient). The hybrid model of PNN and RBFNN performed better than all [ 50 ]. The authors have suggested the IoT-based identification and control system in real time.…”
Section: Related Workmentioning
confidence: 99%
“…Real-time detection of COVID-19 using IoT devices emerged during the pandemic. The proposed system in [169] , [174] uses an Internet of Things (IoT) framework to collect real-time symptom data from users. Its purpose is to detect suspected coronavirus cases early, monitor the treatment response of those who have already recovered from the virus, and learn more about its nature by collecting and analyzing relevant data.…”
Section: Resultsmentioning
confidence: 99%
“…Smart technology delivers real‐time, low‐cost, high‐quality healthcare. Aljumah 46 provided a real‐time COVID‐19 ID&C system that uses the IoT platform to gather users' time‐sensitive symptom information to find coronaviruses early, monitor the clinical actions taken by survivors, and collect and analyze the necessary data to demonstrate the virus's existence. Lydia et al 47 proposed an IoT‐enabled FDL‐COVID model.…”
Section: Preliminariesmentioning
confidence: 99%